This preview shows pages 1–2. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.View Full Document
Unformatted text preview: e ). y = x 2 e-x y (x) = 6) If F ( x ) = f ( g ( x )), where f ( 3 ) = 6 , f '( 3 ) = 1 , f '( 1 ) = 1 , g ( 1 ) = 3 , and g '( 1 ) = 5 , find F '( 1 ). 7) If h ( x ) is given below, where f ( 5 ) = 7 and f '( 5 ) = 2 , find h '( 5 ). 8) For what values of r does the function y = e rx satisfy the equation y '' + 7 y ' - 18 y = 0? r = (smaller value) r = (larger value) 9) Find the 30th derivative of y = cos 3 x . 10) The displacement of a particle on a vibrating string is given by the equation below, where s is measured in centimeters and t in seconds. Find the velocity of the particle after t seconds. v ( t ) = cm/s...
View Full Document